Phytoplankton Increase Along the Kuroshio Due to the Large Meander - Lizarbe Barreto, Daniel Andres; Chevarria Saravia, Ricardo; Nagai, Takeyoshi; Hirata, Takafumi (Frontiers in Marine Science, 2021)
The Kuroshio Large Meander (LM) is known to be highly aperiodic and can last from 1 to 10 years. Since a stationary cold core formed between the Kuroshio and the southern coast of Japan off Enshu-Nada and approaching warm saltier water on the eastern side of the LM changes the local environment drastically, many commercially valuable fish species distribute differently from the non-LM period, impacting local fisheries. Despite this importance of the LM, the influences of the LM on the low trophic levels such as phytoplankton and zooplankton have still been unclear. In this study, satellite daily sea surface chlorophyll data are analyzed in relation to the LM. The results show positive anomalies of the chlorophyll-a concentration along the Kuroshio path during the LM periods, 2004-2005 and 2017-2019, from the upstream off Shikoku to the downstream (140oE). These positive anomalies are started by the triggering meander generated off south of Kyushu, which then slowly propagates to the downstream LM region in both the LM periods. Even though the detailed patterns along the Kuroshio region in the two LM periods were different, similar formations of the positive anomalies on the western side of the LM with shallower mixed layer depth are observed. Furthermore, we found clear relationships between the minimum distance from several stations along the coast to the Kuroshio axis and the mean chlorophyll-a anomaly, with significant correlations with the distance from different stations.